Hallmarks of Parkinson's Disease - Alves Da Costa, Cristine (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book gathers a collection of review articles aiming to provide an update of the current knowledge on PD pathogenesis. It notably includes an overview of several key cellular dysfunctions underlying the etiology of Parkinson's disease, including ER stress, mitophagy and alpha-synuclein-linked pathology.